2005
DOI: 10.1177/0269881105048995
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of modafinil on attentional processes in a five-choice serial reaction time test in the rat

Abstract: It is well known that modafinil is an effective wake-promoting agent, but there is growing evidence to suggest that modafinil may also enhance some aspects of cognition. In man, modafinil has been shown to enhance vigilance in sleep-deprived and/or narcoleptic subjects and also to improve executive-type functioning (predominantly inhibitory response control processes) across a variety of human patient population groups. Preclinically, a delay-dependent improvement has been reported with modafinil in a mouse T-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
46
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 34 publications
7
46
1
Order By: Relevance
“…Preclinical studies have also revealed positive effects on neurocognitive performance. Modafinil treatment in normal mice induced a significant improvement in learning and memory, compared to vehicle-treated controls, using spontaneous alternation and serial spatial discrimination T-maze tasks (Beracochea et al, 2001;Beracochea et al, 2003), although it appears to be without effect on the five-choice serial reaction time in rats (Waters et al, 2005).…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Preclinical studies have also revealed positive effects on neurocognitive performance. Modafinil treatment in normal mice induced a significant improvement in learning and memory, compared to vehicle-treated controls, using spontaneous alternation and serial spatial discrimination T-maze tasks (Beracochea et al, 2001;Beracochea et al, 2003), although it appears to be without effect on the five-choice serial reaction time in rats (Waters et al, 2005).…”
Section: Introductionmentioning
confidence: 90%
“…10 approximately 30 minutes before the procedures (Waters et al, 2005). The drug preparations were delivered for a total of 16 consecutive days, commencing 7 days before the first water-maze trial, and continuing until the end of the watermaze protocol.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have reported increased cognition and attention in humans (Turner et al, 2003;Muller et al, 2004) and rodents (Beracochea et al, 2001(Beracochea et al, , 2002(Beracochea et al, , 2003Ward et al, 2004;Waters et al, 2005;Morgan et al, 2007;Shuman et al, 2009;).…”
Section: Modafinilmentioning
confidence: 99%
“…This has yet to be supported by controlled studies in experimental animals; for example, Waters et al (2005) found no improvement in rat performance with modafinil on the five-choice serial reaction time test, a well-documented test of attentional control (Robbins 2002). However, the evidence for a specific SSRT-improving role for modafinil suggests that it may also confer non-attentional benefits because the stopsignal task measures a process with relatively low attentional demands, given the salience of the stop signal.…”
Section: Psychostimulant Effects On Action Inhibition: the Role Of Camentioning
confidence: 99%